Juraj Dalmatinac i Andrija Aleši u Splitu - majstori, radionice i suradnici / Predrag Marković - Marković, Predrag (Array, 2012)
Among the ten best known examples of residential Gothic architecture in Split created in the middle of the 15th century, the Large and Small Papalić Palaces stand out for their degree of preservation and the quality of their carving and statuary. In the previous literature, they have been ascribed to Giorgio da Sebenico (Juraj Matejev Dalmatinac) and his workshop, with the proviso that some authors saw his role not only as the designer of these complexes but also as the sculptor responsible for the production of the most important carvings and statues, above all for the grand portals. Following up some recently discovered archival documents that connect Nikola Papalić with Andrija Aleši and also earlier suspicions concerning the attribution to Giorgio of the reliefs with angel shield bearers in the lunette of the Small Papalić Palace, Emil Hilje not very long ago voiced the suggestion that »instead of the practice to date of the better works in the complex of Split residential architecture being ascribed to Giorgio da Sebenico and those of a somewhat weaker visual expression to Andrija Aleši, it would be more appropriate actually to ascribe to Aleši the highest quality pieces, and the somewhat lower quality works to his associates and assistants«. This rather general conclusion, which essentially modifies previously held views about the artistic position of the Albanian master has been backed up by the same writer with possible interpretations of some other documents from the notary’s office in Split, from which it can be seen that Andrija Aleši, frequently taking on other craftsmen, supplied parts of the masonry for the building of the houses of some of the leading members of the Split patriciate and the richer burgher class. It is worth pointing out that the author most probably arrived at just this conclusion prompted by the opinions of some other researchers about certain »not-Giorgio da Sebenico features« of the relief in the lunette of the Small Papalić Palace, while he himself had skipped any analysis not only of this piece but of all others that might ultimately have led to such an essentially modified evaluation of the position of Aleši in the history of art. As against this viewpoint, by detailed formal and stylistic analysis of the relief and by comparison of it with other works by both Giorgio and Aleši, it can be ascertained that the angel shield-bearers are to the greatest extent the work of Giorgio da Sebenico own hands. As in some other pieces of his, in this too there are traces of some other hand, which can be seen in the slightly different, softer and more rounded modelling of the heads ; however, it cannot be identified as the work of Aleši, rather, more probably, of some unknown assistant. The rest of the architectural decoration of the Small Papalić Palace, which in essence was created by the modernisation of an older house in Romanesque-Gothic style, shows in its heterogeneity marks of the typical early »Giorgio da Sebenico style of decoration« as well as typical signs of having been produced in the workshop. Thus as a whole it can be considered a production of Giorgio da Sebenico »Split workshop«, which because of the closeness of the quarries on Brač should be only provisionally linked with Split. Because of the characteristic morphological features of the exuberant leafed capitals on the jambs of the portal, which would later, in fact as early as the Large Papalić Palace, evolve into the familiar »Giorgio da Sebenico and Aleši« type of capital, it can be assumed that the remodelling of this house was the first in a series of Giorgio jobs for members of the Split nobility and wealthy bourgeoisie, more or less in parallel with or just before the end of the building of the Chapel of the Blessed Arnerius (Rainer) (1444-1448). And in the light of fairly convincing circumstantial evidence that in the early 1440s Aleši worked on Šibenik Cathedral, too, only as a master carver of the decorative parts, and that some of the details on the Small Palace (the band on the neck of the mullions of the two-light windows) are to be found on later Aleši works (the large mullioned windows in the Large Cipiko Palace in Trogir), we can conclude that as a member of Giorgio da Sebenico »Split workshop« at the beginning he participated only in the making of architectural decoration. Since in those years Giorgio had frequent contacts with Toma Papalić, it might also be concluded that what is concerned is the modernisation of the very house that in 1447 Toma bought in the new part of the city, in order to connect it with the older family house located on the southern side. Although no traces of the work of Andrija Aleši on the Small Papalić Palace can be recognised with any certainty, we can conclude that their collaboration was stepped up after in 1448 Giorgio da Sebenico confided to Aleši the building of the Chapel of St Catherine in the church of the Dominicans of Split, and the same year he himself took on the making of the tomb and chapel of St Anastasius in Split Cathedral. Some other works clearly created in those years by their joint endeavours – the choir screen in the Church of St Francis in Zadar (1444-1449) and the contract that Aleši entered into in 1452 with Giorgio for the making of a large part of the decorative sections of the Loggia dei Mercanti in Ancona – also lead us to the conclusion that they were long-standing collaborators. Perhaps the clearest testimony to their collaboration during these years is provided by the monumental four-light mullioned window of the Large Papalić Palace, on which Aleši carved a waist-length figure of an angel supporting a shield with the coat of arms of the Papalić family. A comparison of that sculpture, which has long been interpreted as a production of the »school of Giorgio da Sebenico«, with other Aleši reliefs – an angel shield bearer from the Radman House in Omiš and angels at the scene of the Baptism of Christ on the facade of the baptistery of Trogir Cathedral (of about 1467) – unimpeachably confirms, I believe, that in their flat heads, small eyes and slender triangular noses the same sculptural style is to be seen. As many researchers have earlier established, apart from the big courtyard portal with the marble lunette in which Giorgio da Sebenico left one more mark of his virtuosity as a sculptor, the other parts of the masonry and statuary of the Large Papalić Palace – the interior staircase, the entry door on the first floor, the neighbouring two-light mullioned window and the courtyard loggia – can be ascribed to his workshop in which again, but now because of the already standardised forms of the »Giorgio da Sebenico and Aleši« capitals, Andrija Aleši might well have taken part. The other parts of the masonry are of considerably poorer quality and, as is shown by the less-than-mediocre execution of the leafy capitals of the single-light windows that in a pair symmetrically articulate the first and second floors of the southern facade of the palace, do not indicate even any reasonably close links with the school of Giorgio da Sebenico ; we can consider them mere pallid reflections of his work, that is, the productions of local carvers. This much poorer quality group of architectural decorations is placed on peripheral parts of the building, much less accessible to the eye, and apart from telling of a certain pragmatism of the client, who most likely was spurred by a reduction of the costs of workmanship to give up on engaging the workshop of Giorgio da Sebenico, suggests the conclusion that it was created independently of the earlier mentioned productions of his workshop, and as a result some other, perhaps contemporaneous, commission. The practice of taking on craftsmen of various specialities in the building of Split housing architecture, builders, carvers and carpenters as well as other groups of stonecutters who made various parts of the stone furnishing (the balusters for the stone balustrade for the house of the merchant Ventura) is revealed to us by documents that were published by Hilje. The position of key elements of architectural decoration made by Giorgio da Sebenico and his workshop confirm the viewpoints of numerous authors already made that he was also the author of the design pursuant to which the architectural complex of the Large Palace took on the typical lines of the grand Venetian house. This would tend to contradict the latest propositions that it is the house of Zancius Nikolin de Albertis that is concerned, the house that in 1493 he left to Petar, the son of Dominik Nikolin Papalić. Correlating some newly discovered archival documents, E. Hilje (2005) was the first to arrive at this assumption. According to a judgement of 1456, Aleši was supposed to complete the balconies on the house of Zancius de Albertis, leading member of the Split patriciate, with whom, in a couple of other documents, a close associate of Aleši, the Split carver Marin Veseljković was connected. Paying attention to the fact that Zancius de Albertis was a close relative of one branch of the Papalić family, that of Nikola Dominikov Papalić, and that on the lintel of the staircase portal of the Large Palace an inscription was subsequently carved - HAEC ٠QUIBUS٠ IANCI / CVI FORTVNA FAVEBIT (For whom is this Janko? For him whom Fortune favours), the same author suggested the possibility that the Large Papalić Palace was in fact originally owned by Zancius de Albertis and that only after his death in 1493 did it come into the hands of the Papalić family. This merely attractive hypothesis, as Hilje himself called it, was adopted in its entirety and considerably developed by R. Bužančić (2012), arguing that with a change of the owner, on the lintel of the portal at the top of the external staircase, came not only the subsequent carving of the inscription but also the secondary carving of the earlier coat of arms of the de Albertis family. In order to support his thesis that the house was originally that of Zancius de Albertis, Bužančić included in these subsequent modifications at the end of the 15th or in the early 16th century the relocation or subsequent insertion of a marble lunette with the Papalić coat of arms to or into the large courtyard portal that, unlike the lunette, was in his opinion a production close to the Aleši workshop. Undoubtedly, many elements would tend to support such a conclusion, above all the subsequently carved inscription on the lintel of the portal and the re-carved coat of arms, but against it is still the fact that the large four-light window is still in situ and the Papalić coat of arms on it has not been secondarily carved. Apart from that there is a very small possibility of there being one more almost identical courtyard portal of the Papalić family from which at the end of the 15th century a marble lunette could have been taken. Finally the exuberant and lively animated leaves in the lunette clearly reveal temperament of Giorgio da Sebenico and the virtuosity of his chisel. What is more the other decorations on the frame of the portal are in no way inferior to them, particularly the masterly carved capitals, which in their quality outstrip all other similar works of Aleši. Finally, pursuant to the already mentioned business links established to have existed between Giorgio da Sebenico and Aleši, and to the perception of the considerable share of the many assistants and their subcontractors, it should be pointed out that during the solution of the problem of authorship of masonry and statuary, attention should be paid more frequently to the artisan and craft nature of this production, and the currently rather neglected or abandoned concepts of workshop, assistant or associate that correspond more to their common achievements should be more often employed.